Hypoxia in Leishmania major skin lesions impairs the NO-dependent leishmanicidal activity of macrophages - Mahnke, Alexander; Meier, Robert J.; Schatz, Valentin; Hofmann, Julian; Castiglione, Kirstin; Schleicher, Ulrike; Wolfbeis, Otto S.; Bogdan, Christian; Jantsch, Jonathan (Journal of Investigative Dermatology, 2014)
Cure of infections with Leishmania major is critically dependent on the ability of macrophages to induce the type 2 nitic oxide (NO) synthase (NOS2) that produces high levels of NO in the presence of ample oxygen. Therefore, we analyzed the oxygen levels found in leishmanial skin lesions and their effect on the NOS2-dependent leishmanicidal activity of macrophages (M?). When L. major skin lesions of self-healing C57BL/6 mice reached their maximum size, the infected tissue displayed low oxygen levels (pO2 21 Torr). M? activated under these oxygen tensions failed to produce sufficient amounts of NO to clear L. major. Nos2-deficient and hypoxic wild-type macrophages displayed a similar phenotype. Killing was restored when M? were reoxygenated or exposed to a NO donor. The resolution of the lesion in C57BL/6 mice was paralleled by an increase of lesional pO2. When mice were kept under normobaric hypoxia, this caused a persistent suppression of the lesional pO2 and a concurrent increase of the parasite load. In Nos2-deficient mice, there was no effect of atmospheric hypoxia. Low oxygen levels found at leishmanial skin lesions impaired the NOS2-dependent leishmanicidal activity of M?. Hence, tissue oxygenation represents an underestimated local milieu factor that participates in the persistence of Leishmania.
EVALuna2:7645